S1_5 It’s a bird! It’s a plane! No, it’s a pig! - Mahmood, Ridda; Gajendran, Arcchana; Madden, Shannon (Physics Special Topics, 2017)
It's likely we have all used the common adynation 'when pigs fly' at some time in our lives, but in this article we question how pigs may fly. Using a Strouhal number of 0.2 we calculated the combined minimum surface area of the wings required for a wild pig to fly to be 5.13 m^2.